Unanticipated diagnosis- intraparenchymal leiomyoma of the breast: case report - Goncalves, Ines C.; Ventura, Nuno; Valente, Tania; Ferreira, Gonçalo; Torgal, Margarida; Amado, Cristina; Santos, Miguel C. (International Surgery Journal, 2020)
Smooth muscle neoplasms are uncommon, particularly if we are talking about the mammary gland. We report a case a case of a 38-year-old female with an 11.6 mm right breast nodule. A wire-guided surgical excision was performed and the histopathologic and immunohistochemical studies revealed a leiomyoma. There are no radiological criteria to allow the diagnosis of smooth muscle neoplasm and histopathological evaluation is the definitive diagnostic method. Despite being a benign neoplasm, it may mimic malignancies and therefore present a diagnostic challenge.